2020
DOI: 10.3390/ma13122782
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cadmium, Manganese and Lead Ions from Aqueous Solutions Using Spent Coffee Grounds and Biochar Produced by Its Pyrolysis in the Fluidized Bed Reactor

Abstract: The adsorption process of cadmium ions (Cd), manganese ions (Mn) and lead ions (Pb) onto the spent coffee grounds (SCG) and activated spent coffee grounds (biochar, A-SCG) was investigated. The SCG activation was carried out in the pyrolysis process in a fluidized bed reactor. scanning electron microscope (SEM) with energy dispersive X-ray spectroscopy (EDX), Fourier-transform infrared spectroscopy (FTIR), Brunauer–Emmett–Teller (BET) measurements and CHN analysis were used in order to define the differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 27 publications
(37 reference statements)
3
21
0
Order By: Relevance
“…As shown in Table 2 , the pseudo-second-order kinetics model with a higher correlation coefficients value (R 2 = 0.96, 0.80) fitted better than the pseudo-first-order kinetics model (R 2 = 0.89, 0.68), suggesting that the adsorption behavior of HTC-NH 2 towards Cr(VI) corresponded to pseudo-second-order kinetics. These results indicated that the adsorption rate of Cr(VI) onto adsorbent was mainly determined by the chemical adsorption process, consistent with the previous results [ 45 , 46 , 47 ]. This is showed that the adsorption capacity of HTC-NH 2 was up to 18.33 mg/g, which is much higher than that of HTC (13.68 mg/g).…”
Section: Resultssupporting
confidence: 92%
“…As shown in Table 2 , the pseudo-second-order kinetics model with a higher correlation coefficients value (R 2 = 0.96, 0.80) fitted better than the pseudo-first-order kinetics model (R 2 = 0.89, 0.68), suggesting that the adsorption behavior of HTC-NH 2 towards Cr(VI) corresponded to pseudo-second-order kinetics. These results indicated that the adsorption rate of Cr(VI) onto adsorbent was mainly determined by the chemical adsorption process, consistent with the previous results [ 45 , 46 , 47 ]. This is showed that the adsorption capacity of HTC-NH 2 was up to 18.33 mg/g, which is much higher than that of HTC (13.68 mg/g).…”
Section: Resultssupporting
confidence: 92%
“…The data of the Redlich–Peterson model presents a higher value of R 2 , implying the monolayer and multi-layer adsorption process between the M/P-0.1-600-2 and CO 2 . In addition, Fick models and linear driving force (LDF) [ 38 ] were also conducted to evaluate the adsorption kinetics of M/P-0.1-600-2, as shown in Figure 5 c. The fitted parameters ( Table S5 ) shows that Fick models possesses a higher R 2 and lower χ 2 coefficient value than that of LDF, indicating that the CO 2 adsorption kinetics of M/P-0.1-600-2 follows the Fick model, suggesting that the physical adsorption plays a major role in the adsorption process [ 39 ]. The regeneration property is significant for solid adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…According to the principle of pseudo-second-order model, it was inferred that the adsorption of Pb 2+ by P/ACs was dominated by chemisorption, similar to the results of Chwastowski et al [ 30 ]. The chemisorption such as some electron transfer or sharing between the Pb 2+ and the adsorbents may be the rate-limiting step [ 31 ]. In addition, when the experimental results were fitted into the intraparticle diffusion, the plot exhibits a multi-linearity relationship ( Figure 5 D).…”
Section: Resultsmentioning
confidence: 99%